Geometric science of information : 4th International Conference, GSI 2019, Toulouse, France, August 27-29, 2019, Proceedings /: 4th International Conference, GSI 2019, Toulouse, France, August 27-29, 2019, Proceedings. (2019) - Unknown
No abstract available